MEMBANGUN SEKOLAH DASAR UNGGUL: TRANSFORMASI BUDAYA MUTU SEKOLAH DASAR MELALUI MODEL KEPEMIMPINAN VISIONER - Suriansyah, Ahmad; Amelia, Rizky; Revia Rafianti, Wahdah; Ngadimun, Ngadimun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to analyze the effectiveness of a Workshop on School Quality Culture Development based on research findings on visionary leadership conducted in Barito Kuala Regency as part of a Community Service Program. The activity was implemented at SDN Sungai Seluang Pasar, involving one principal and nine teachers through preparation, implementation, and evaluation stages. A participatory-collaborative approach was employed, including conceptual training, technical workshops, role play, and mentoring in developing action plans and quality evaluation instruments. The results indicated a 35% average increase in participants’ understanding based on pre-test and post-test scores. Furthermore, 90% of participants expressed readiness to implement the formulated action plans and established an internal quality assurance team. The workshop not only improved technical competencies in data-based planning and evaluation but also strengthened collective commitment to sustaining a quality culture. These findings demonstrate that integrating visionary leadership research into community service initiatives effectively supports the transformation of primary schools toward systematic and sustainable quality practices.